The influence of the local structure of Fe(III) on the photocatalytic activity of doped TiO(2) photocatalysts - Bajnóczi Éva Gabriella; Balázs Nándor; Mogyorósi Károly; Srankó Dávid Ferenc; Pap Zsolt; Ambrus Zoltán; Canton Sophie E.; Norén Katarina; Kuzmann Ernő; Vértes Attila; Homonnay Zoltán; Oszkó Albert; et al. (2011)
Fe(III)-doped TiO(2) based heterogeneous photocatalysts were prepared by the sol-gel technique (S samples) or flame hydrolysis (F samples). In photocatalytic phenol decomposition, the undoped F-sample performed much better, than the undoped S one. However, for the S samples, photocatalytic activity first increased with the increasing Fe(III) concentration, and then passed through a maximum, while Fe(III)-doping in F samples significantly decreased it, even at the smallest dopant level. Since the same dopant caused opposite photocatalytic effects in the two series, their structure was systematically compared to identify the underlying chemical and/or physical reasons. The photocatalysts were first characterized by AAS, DRS, XRD and TEM methods and it has been shown that the differences in the photocatalytic activity cannot be explained by the minor variations in the bulk structural properties of TiO(2). Mossbauer and XP spectroscopic measurements performed on representative samples qualitatively proved that the local structure of Fe(III) is different in the two series. To quantify these effects, Fe-K edge X-ray absorption measurements were performed. From the pre-edge and XANES region it was learnt that Fe(III) was present in a distorted octahedral environment in both series, however, the extent of distortion is much more significant within the S than within the F one. Information obtained from the EXAFS region indicated that the structure of Fe(2)O(3) was much more ordered in the F-series then in the S one and vacancies were more abundant in the S than in the F series. Moreover, the geometry around Fe(III) systematically varied within the S-series, which could explain, why photocatalytic activity passed through a maximum with the increasing Fe(III) concentration in these samples. (C) 2011 Elsevier B.V. All rights reserved.